Does the cost behavior remain sticky? a 20-year literature review of cost stickiness - Amanda, Diva Putri; Hakim, Tito IM. Rahman; Zuhdi, Rahmat (Journal of Accounting and Investment, 2024)
Research aims: This study aims to describe the development of cost stickiness research over the past twenty years globally and presents a future research agenda.Design/Methodology/Approach: The method used in this study is a systematic literature review with a final research sample of 91 articles from 42 international journals indexed by Scopus Q1-Q4 and 20 articles from national journals indexed by SINTA 1-4. Research findings: This research found annual developments and fluctuations in cost stickiness research topics in international and national journals. Mapping of cost stickiness research exhibits that (1) the dominating antecedent variable is revenue change, (2) the popular consequence variable is accounting conservatism, (3) the most widely used theory is cost stickiness theory, (4) the majority of cost stickiness research used quantitative methods with secondary data, (5) the widely used population is public sector or profit-oriented companies, and (6) the proxy dominating cost stickiness research is SGA.Theoretical contribution/Originality: This research mapping is based on six critical aspects of cost stickiness and provides several suggestions for future research. It is expected that future research related to cost stickiness can use this research as a reference and inspiration. Research limitation/Implication: Several websites in national journals indexed by SINTA 1-4 could not be accessed due to errors, limiting the number of research samples in national journals. Hence, future research can expand the search for articles in SINTA 1-6 or through other pages/portals (such as Web of Science) to more comprehensively describe the development of cost stickiness research.